Alternative Learning Strategies for Mathematics Education - G.C., Laxmi (ILAM इलम, 2024)
Correction: On 18th July 2024 the author's name was changed from Laxmi Aryal TO Laxmi G.C. This study explores to identify alternative learning strategies of the mathematics achievement and enrollment in mathematics education. The COVID-19 pandemic has further highlighted the need for such strategies, with an increasing demand for innovative learning. This study also aims to investigate students' perceptions and practices of alternative learning strategies and provide valuable insights for educators and policymakers. The methodology involves a comprehensive literature review spanning from 1978 to 2021, with an attention on relevant books, articles, and research reports. The study investigated best practices and effective strategies in mathematics education including Inquiry-Based Learning (IBL), Technology-Based Learning (TBL), Edu-Lab model, Flipped Learning Model, Problem-Based Learning (PBL), Cooperative Learning (CL), and Collaborative Learning (CL). These strategies have shown hopeful results in motivating students, reducing anxiety, and improving mathematical knowledge. The study proposes a paradigm shift towards student-centered learning and the integration of innovative technologies for mathematics education in the 21st century.